Influence of Sociodemographic Variables on Dental Service Utilization and Oral Health Among the Children Included in the Year 2001 Spanish National Health Survev - Miguel Angel Tapias-Ledesma, MD PhD; Rodrigo Jimenez, MD, PhD; Pilar Carrasco Garrido, PhD; (Blackwell Synergy, 2005)
To ascertain the possible influence of sociodemographic variables on dental service utilization and oral health among Spanish children.